Kamus Mandarin lengkap bergambar untuk anak : Indonesia-Inggris-Mandarin / Yi Ying, Tirta Nugraha Mursitama ; editor Benedicta Rini W. - YI, Ying; Tirta Nugraha Mursitama; Benedicta Rini W. (Andi, 2014)
viii, 144 hlm. : ilus. ; 28 cm